On the potential of regenerative braking of electric buses as a function of their itinerary - Perrotta, Deborah (2012)
This paper proposes a mathematical model for an electric bus powertrain, implemented in a simulation platform. We intend to analyze the consumption of energy according to the route specifications and other performance measures. The potential for regenerative braking will be evaluated for different routes, since it depends significantly on them. It is expected that a "pattern" can be observed in that concerning the potential of the system to recover back some of the energy spent in its operation. Moreover, the use of supercapacitors to make this braking energy absorption is investigated.